On the Generalized Hardy Spaces - M. Fatehi (Abstract and Applied Analysis)
We introduce new spaces that are extensions of the Hardy spaces and we investigate the continuity of the point evaluations as well as the boundedness and the compactness of the composition operators on these spaces.